2018
DOI: 10.1039/c7ra10981d
|View full text |Cite
|
Sign up to set email alerts
|

On the role of peptide hydrolysis for fibrillation kinetics and amyloid fibril morphology

Abstract: Self-assembly of proteins into amyloid-like nanofibrils is not only a key event in several diseases, but such fibrils are also associated with intriguing biological function and constitute promising components for new biobased materials. The bovine whey protein b-lactoglobulin has emerged as an important model protein for the development of such materials. We here report that peptide hydrolysis is the rate-determining step for fibrillation of b-lactoglobulin in whey protein isolate. We also explore the observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
93
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 66 publications
(103 citation statements)
references
References 47 publications
(93 reference statements)
10
93
0
Order By: Relevance
“…AFM images of the samples showed that the majority of the PNFs are rather short (typically between 0.1 and 0.5 mm) and highly curved (Fig. 2), similar to brils reported for the whey protein b-lactoglobulin under certain conditions 8,36,37 as well as other proteins. 13,34,38,39 However, a few longer (>1 mm) and more straight brils could also be observed.…”
Section: Pnf Formation From Spisupporting
confidence: 80%
See 4 more Smart Citations
“…AFM images of the samples showed that the majority of the PNFs are rather short (typically between 0.1 and 0.5 mm) and highly curved (Fig. 2), similar to brils reported for the whey protein b-lactoglobulin under certain conditions 8,36,37 as well as other proteins. 13,34,38,39 However, a few longer (>1 mm) and more straight brils could also be observed.…”
Section: Pnf Formation From Spisupporting
confidence: 80%
“…More likely, it is related to the length and the physicochemical properties of the peptide segments as suggested for whey PNFs in our previous work. 8…”
Section: Fibril Formation Of the Peptide Segmentsmentioning
confidence: 99%
See 3 more Smart Citations